Integration Between Qauliyah and Kauniyah Verses With Science And Technology In Islamic Education: Integrasi Antara Ayat Qauliyah Dan Kauniyah Dengan Ilmu Pengetahuan Dan Teknologi Dalam Pendidikan Islam - Wakit , Saipul; Suyitno, Margiyono; Dacholfany, Muhamamd Ihsan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The advancement of science and technology has reshaped modern civilization, yet without a moral foundation, it risks diminishing human values. Specific Background: Islamic education, rooted in divine revelation, emphasizes a balanced integration of knowledge from both the Qur'an (Qauliyah verses) and natural phenomena (Kauniyah verses) to cultivate holistic human development. Knowledge Gap: Despite the growing body of research on religious and scientific integration, few studies explore the epistemological synthesis of revelation and empirical observation in shaping Islamic educational frameworks. Aims: This study aims to analyze the integration of Qauliyah and Kauniyah verses with science and technology to build an educational model grounded in both spiritual and intellectual excellence. Results: Through literature review, the study finds that integrating both types of verses enriches pedagogical methods, strengthens students' engagement, and inspires Muslim scholars to develop contextual, character-based education amid global technological challenges. Novelty: The research introduces a conceptual paradigm where scientific inquiry becomes a medium for deepening faith and ethical awareness, rejecting the dichotomy between religious and secular knowledge. Implications: The findings suggest that integrating revelation and empirical knowledge can form a value-based curriculum in Islamic education, offering a viable response to secularization and moral decline in global education.Highlight : Integration of Qauliyah and Kauniyah verses strengthens Islamic education foundations. Islamic education should combine revealed values with scientific knowledge. Science and technology serve as a medium for deeper reflection and faith. Keywords : Integration, Verses, Qauliyah, Kauniyah, Science and Technology